Pengaruh Kemudahan Penggunaan, Kemanfaatan, dan Kepercayaan Terhadap Keputusan Penggunaan E-wallet (DANA) di Kota Malang(Studi Kasus Pada Masyarakat di Kota Malang) - Ramalda, Nauval; Widarko, Agus; Slamet, Afi Rachmat (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to examine the influence of ease of use, usability, and trust on users' decisions in using e-wallet (DANA). Technological advances have changed people's needs for safe and fast payment systems. Along with the increase in internet users via smartphones, various payment applications have emerged which have become a trend among society, especially the younger generation. E-wallets have become a very popular digital payment option in Indonesia, one of which is DANA. The research methodology used is explanatory research with a quantitative approach. This research focused on people living in the city of Malang, with a sample size of 100 respondents determined using the Slovin formula. To test the research hypothesis, multiple linear regression analysis was used with the help of the SPSS 23 analysis tool. The test results showed that both simultaneously and partially, perceived ease of use (X1), usefulness (X2), and trust (X3) had a positive and significant influence on usage decision (Y). Keywords: Perception Ease of Use, Usefullness, Trust, Decision to Use